Detention of Asylum Seekers in Mexico - Kuhner, Gretchen (Refuge: Canada’s Journal on Refugees, 2002)
Mexico ratified the Convention relating to the Status of Refugees and the 1967 Protocol in April 2000. While Regulations establishing a mechanism for eligibility determination were issued at the same time, the Mexican government began a transitional process to take over eligibility in March 2002. Prior to that time, the UNHCR had been recognizing refugees under its mandate. As of this writing no national policy regarding the detention of asylum seekers has been established, nor have refugee advocates begun to pressure the government to comply with Article 31 of the Convention. Rather, whether an asylum seeker is detained during the eligibility process depends in part on the place and timing of the request as well as on the knowledge and goodwill of the migration authority.